Metode Maut dan Waspas Menentukan Mahasiswa Berprestasi di Universitas Bhayangkara Jakarta Raya dengan Pembobotan ROC - Bernadus Gunawan Sudarsono; Raditya Galih Whendasmoro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Becoming an outstanding student in higher education is a positive and proud achievement, reflecting the national education goal of developing students' potential to become educated, creative, and democratic and responsible citizens. Determining outstanding students faces obstacles when prospective candidates excel in some criteria but do not meet the standards in other criteria. To help the evaluation team, an effective decision support system is needed. The Multi-Attribute Utility Theory (MAUT) method with ROC weighting was used to convert various interests into numerical values ​​on a scale of 0-1, with the results showing that student Erwin Sulistiono (A4) had the highest utility value, namely 0.8975. For comparison, the Weighted Aggregated Sum Product Assessment (WASPAS) method was also applied, combining the Weighted Sum Model (WSM) and the Weighted Product Model (WPM), which gave consistent results with MAUT, showing that both methods provide an objective approach in determining outstanding students, although WASPAS with ROC weighting offers higher accuracy by combining the advantages of two scoring approaches.